Ink Trails II : Michigan's Famous and Forgotten Authors - Dempsey, Dave, 1957-; Dempsey, Jack, 1952- (Book collections on Project MUSE., 2016)
"From authors of bodice rippers and gallant figures to hometown poetry, hearty men, and tales of American originals, the history of literature in Michigan is deep and rich. The Wolverine State has been the birthplace, home, and inspiration to a tremendous number of men and women of letters, both the well-known and the obscure. Ink Trails II tells the stories of these fascinating and diverse writers whose talent is inextricably linked to Michigan. Exploring the hidden treasures of otherwise forgotten authors while also acknowledging the Michigan-set stories of giants like Hemingway, Dave and Jack Dempsey delve into the state's literary heritage, as robust, diverse, and inexhaustible as the natural beauty of the place that nurtured it. This second volume of "ink trails" continues to tell the story of the remarkable writers, powerful words, and sublime nature of Michigan in the same well-researched and entertaining prose as the first"--